Improving the stability of diesel emulsions with high pyrolysis bio-oil content by alcohol co-surfactants and high shear mixing strategies - Cruz, Louie Angelo D.
Bio-oil from biomass pyrolysis is a clean, sustainable and renewable energy resource. In this study, the emulsification of pyrolysis bio-oil in diesel fuel using a commercial emulsifier (Atlox 4914) and three alcohols (methanol, ethanol and n-butanol) as co-surfactants is investigated, with emphasis on emulsion stability and minimum emulsifier usage. Results show that the higher the bio-oil content, the lower the relative content of surfactant required for successful emulsification. The presence of alcohol co-surfactants into the emulsions, especially for those with higher bio-oil content, significantly improves emulsion stability (methanol > ethanol > n-butanol). These findings are attributed to the differences in alcohol molecular structure, polarity, viscosity and density. In this study, the influence of mixing strategy on emulsion stability is also evaluated. The performance of a vortex mixer is compared with that of an inexpensive commercially available blender. The vortex mixer provided better short-term mixing due to a more uniform energy distribution but the off-the-shelf blender gives superior emulsion stability. The blender mixing method offers a simple, low-cost and high-speed mixing that can provide the necessary mechanical energy input for successful emulsification. Overall, the present study gives useful insights into the production of bio-oil in diesel emulsions with high bio-oil content.